Hashtag #2019GantiPresiden: Sentimen Anti-petahana dan Orientasi Politik Pemilih Pemula menghadapi Pilpres 2019 di Pematangsiantar (Universitas Medan Area, 2018)
The aim of the research is to understand the emergence of hashtag#2019ChangePresident and the political orientation of the new voters face the 2019 Presidential Election. Hashtag#2019 ChangePresident through social media, t-shirts, stickers, as well as declaration of the hashtag#2019ChangePresident in various regions in Indonesia. Hashtag#2019ChangePresident is a coercion of opinion, Anti-incumbent sentiments and deconstruction of President Incumbent's success stories in the 2019 Presidential Election. This movement targets Beginner Voters and productive age who live in urban areas. The main problem in this research is the hashtag#2019ChangePresident has an impact on the political orientation of the new voters facing the 2019 Presidential Election? The theory used is the strategic speaker from Lee and Pinker. Data collection was conducted through in-depth interview techniques and Likert Scale questionnaire distribution to 100 research informants. The results showed that the hashtag#2019ChangePresident impacted 17 percent of research informants. The contribution of this study confirms that the hashtag#2019ChangePresident has an impact as a means of driving opinions to strengthen the Anti-incumbent sentiment and deconstruction of the incumbent president's success stories.